Differences in memory function between 5-HT1A receptor genotypes in patients with major depressive disorder. (19th January 2016) - Wesnes, Keith A.; Hopkins, Seth C.; Brooker, Helen J.; Koblan, Kenneth S.
Abstract : Background: While extensive literature on the role of the serotonin receptor 1A (5-HT1A-R) in cognition exists, the findings are largely from animal studies. There has been little research conducted into 5-HT1A-R genotypes and cognitive function in humans. This article evaluates the role of 5-HT1A-R genotypes on the profile of cognitive function in patients with major depressive disorder (MDD). Methods: The study sample was 455 MDD patients aged between 18 and 55 years. They had enrolled into a clinical trial and were tested prior to dosing on the baseline study day using the CDR System, an integrated set of 3 attention tests, 2 working memory tests, and 4 episodic memory tests. 5-HT1A-R genotyping for (SNP ID rs6295) had been conducted during the study screening period. Results: Validated factor scores were derived from the 9 tests. It was found that patients with the C/C genotype for the C(1019)G polymorphism of the 5-HT1A-R were significantly superior in retaining and retrieving information, in both working and episodic memory, than those with either the C/G or the G/G genotypes. No differences were found in measures of attention or in the speed of retrieval of information from memory. Conclusions: This is, to our knowledge, the first relationship found between objective tests of cognitive function and 5-HT1A-R genotypes in MDD.